Dynamic ageing of an oxygen-containing monolayer at platinum and gold electrodes in aqueous acid solutions - Tacconi, Norma R. de (1977)
It is already well established that oxygen-containing species electrochemically formed in the monolayer range on Pt and Au electrodes in acid electrolytes undergo ageing processes which are easily evidenced by a potential shift of the corresponding electroreduction current peak observed under a cathodic linear potential sweep. During the ageing process the oxygen containing surface species undergoes a change into another one involving a more stable configuration but without any detectable change of the oxygen/surface metal atomic ratio. The ageing process takes place simultaneously with the electrosorption of oxygen and its contribution can be reasonably controlled during the electro° desorption process as is the case, for instance, when the surface species is allowed to stay under open circuit for a certain time after its electrochemical formation.